(G'/G²)-expansion Solutions to MBBM and OBBM Equations (Journal of Partial Differential Equations, 2015)
" In this paper,with the aid of symbolic computation, themodified Benjamin- Bona-Mahony and Ostrovsky-Benjamin-Bona-Mahony equations are investigated by extended (G'\/G2)-expansion method. As a consequence, some trigonometric, hyperbolic and rational function solutions with multiple arbitrary parameters for the two equations are revealed, which helps to illustrate the effectiveness of this method."